An Analysis of Health Benefits of Exercise (International Journal of Innovative Research in Engineering & Management, 2023)
Physical activity is defined as anybody exertion that necessitates exertion & is produced by  muscle contraction. Phrases "physical activity" & "workout" are not interchangeable. Workout is  subcategory of vigorous exercise that is structured,  repetitive, & purposeful. "A healthy brain equals a good  physique." It means that if person is sluggish, slow, or  sickly, he would be unable to do his or her duties  successfully & quickly. Exercise & physical activity on  routine basis may help you stay healthy, energetic, & independently as you age. Exercise is essential in  eliminating health issues including stroke. Numerous  studies have demonstrated health benefits of regular  exercising. This article investigates facts on benefits of  exercise for all biological systems. Exercising regularly  can help reduce stress & anxiety, boost happy hormones,  boost self-esteem, exp& brain capacity, improve  memories, & build our bones & muscles.
Keywords: Exercise; Energy; Physical Activity; Yoga